قضايا المرأة في آثار الإمام ابن باديس - لعور، ربيع بن محمد بن الربيعي (الجامعة الإسلامية العالمية - مجمع البحوث الاسلامية, 2012)
This paper studies some important issues concerning the reformation of women discussed in the writings of Abdul am d Ibn-e- B d s who was an emblematic figure of Islamic Reform Movement in Algeria. The writer has classified these issues under six titles: Appointment of women to political and judicial offices, women's education, women's dress code, women's specific functions, mixed sex lifestyle and birth control. These subjects have been treated both in the Islamic legal Context, and through a realistic analysis of the Algerian Society, which is not essentially different from those of most Muslim countries. This paper concludes that a heavy loss has affected Muslims consequent upon ignoring the directives of their reformer scholars such as Ibn-e- B d s, and being carried away instead by the different deceptive mirages that seemingly showed themselves as paths of progress while in reality these only spelt disaster.
Keywords: ابن باديس، عبدالحميد -- الفكر الإسلامي -- المرأة في الإسلام -- حقوق المرأة